‘Gay Space is wherever I am’: The Outlines of Pink Consumption Spaces in Croatia - Jakovčić, Martina; Mak, Karlo (Geographica Pannonica, 2023)
Based on the dialectical relationship between queerness and homonormativity, the aim of this paper was to outline the spatial framework of pink consumption in Croatia. Given that the LGBT community is a specific and sensitive social group, qualitative research methods were used. After calculating the gay index and establishing that the city of Zagreb provides the most favourable spatial context for studying pink consumption, we used the interview method to collect qualitative data. The sample was collected using the snowball technique (N = 14). The research established there are only few pink consumption places in Zagreb, that they do not even appear in all consumption systems, and that without exception they are located in the central part of the city. Although it cannot be claimed that these are completely homonormative places, indications of social exclusivity and sexual conservativism were detected. Therefore, it has been shown that even fundamentally inclusive places can produce normativity, which deprives them of the potential to achieve equality and emancipation of the Zagreb LGBT community.
Keywords: pink consumption; LGBT community; Zagreb; homonormativity